Prosedur Perhitungan Anggaran Upah Tenaga Kerja Langsung di PT. Wijaya Tirta Makmur - Nur Cholilla Dian Tristiana; Lis Setyowati (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
The purpose of this study is to identify the procedure for budgeting direct labor wages of the convection division at PT Wijaya Tirta Makmur. This type of research uses qualitative research. This study used primary data and secondary data. From the observations that have been made, it can be seen that all staff, both office and production, both have an important role in the production process.The results of this study show that the wage system used by PT Wijaya Tirta Makmur for convection division is a wage system based on the number of units of output which can certainly increase company productivity.